Calibration Research: Where Do We Go from Here? - Bol, Linda; Hacker, Douglas J. (Frontiers in Psychology, 2012)
Research on calibration remains a popular line of inquiry. Calibration is the degree of fit between a person’s judgment of performance and his or her actual performance. Given the continued interest in this topic, the questions posed in this article are fruitful directions to pursue to help address gaps in calibration research. In this article, we have identified six research directions that if productively pursued, could greatly expand our knowledge of calibration. The six research directions are: (a) what are the effects of varying the anchoring mechanisms from which calibration judgments are made, (b) how does calibration accuracy differ as a function of incentives and task authenticity, (c) how do students self-report the basis of their calibration judgments, (d) how do group interactions and social comparisons affect calibration accuracy, (e) what is the relation between absolute and relative accuracy, and (f) to what extent does calibration accuracy predict achievement? To help point the way to where we go from here in calibration research, we provide these research questions, propose research methods, and identify prior, related studies that have shown promise in leading the way to fill these gaps in the literature.